Investment and innovation policy in the context of ensuring the economic security of the state (Journal of Economic Research & Business Administration, 2016)
The article discusses the development of our country’s economy in a world where one the main factors are not having overwhelming natural resources, but creation of innovations based on human mind and theircreative ideas. Therefore, the most important direction of the state policy of the Republic of Kazakhstan is the intensification of the creation processes of intellectual property and the further improvement of their legal protection. Kazakhstan stands at a similar crossroads;however, it must overcome the excessive dependence on exports of raw materials for the restoration of its economy. Economic growth, which based only on this dependence, is going to be unstable in a future. Change in national economy is directly linked to the prospects of technological development. The complexity of the problem lies in the fact that sustainable production process is required to determine not only its main direction, but also the level of technology, which they must achieve.Additionally, the fact that this process requires government support is quite significant.Moreover, almost all sectors of Kazakhstan’s economy have elements of several technological ways, which intertwined with each other and has a unique and close collaboration.
Keywords: Intellectual property; direct and indirect investments; the economic security of the state; the country’s innovation processes.